Mapping EU maritime capacity-building in the Atlantic - Seabra, Pedro; Costa, Rita (Mapping EU maritime capacity-building in the Atlantic, 2021)
This report is grounded by three key objectives. First (1), it aims to provide an updated overview of EU involvement in the Atlantic, by mapping past and present capacity-building initiatives within such a space. Second (2), it adds a particular premium to comparable and verifiable information while ensuring it is made available for further studies on the topic. Third (3), it depicts key trends that illustrate the strengths and weaknesses faced thus far by European capacity-building efforts. Assessments over the effectiveness of EU actions, however, will remain outside of the scope of research. The remaining of the content is structured as follows. The second section briefly tackles the ongoing debate over the capacity-building concept and recaps the official discourse the EU has adopted over the years in order to justify the expansion of its own modus operandi abroad. The third section elaborates on the methodology underpinning the bulk of this mapping exercise, including key criteria of analysis and main data sources. The fourth section concentrates on highlighting the main identifiable trends, together with single case-studies that merit special consideration in the broader discussion over the role of the EU in the Atlantic. We conclude by providing key takeaways that may inform and guide subsequent reports on the topic.